Rancang bangun pengisian air dan penutup botol otomatis berbasis PLC - Putu Rizky Jaya Kusuma; I Ketut Parti; I Ketut Darminta; I Nyoman Mudiana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This automatic water filling and bottle closing system can usually be used in the industrial world, because it can facilitate and save processing time. For this reason, an automatic water filling machine was made to produce packaged drinks that are practical and easy to obtain. In this machine, there are components that play an important role in the operation of this automatic machine, including the Programmable Logic Controller (PLC) which is a control device that can be programmed logically, accepts input, and provides output. In the manufacture of this automatic water filling and bottle closing device, 4 sensors and 1 limit switch are used, each sensor has its own function. The 4 (four) sensors include: conveyor sensor, rotation sensor, bottle closing sensor and reset sensor. The limit switch on this tool functions as a stop motor rotation when the bottle is closed. After several experiments, it took 13 seconds to fill a bottle with a capacity of 600 ml.